MANIFESTATIONS OF EMOTIONAL BURNOUT SYNDROME AMONG MINERS IN THE SOUTH OF KUZBASS - Пестерева, Дина Викторовна; Тапешкина, Наталья Васильевна; Логунова, Татьяна Дмитриевна (Medicine in Kuzbass, 2024)
The study aim was to identify the symptoms of emotional burnout syndrome in miners at coal enterprises in the South of Kuzbass with long work experience in harmful conditions.The subject of the study was the prevalence of emotional burnout syndrome in workers with long labor experience at coal enterprises in the South of Kuzbass.Materials and methods. A survey of 104 miners with occupational diseases and undergoing treatment at the Institute’s Clinic aged from 43 to 67 years with work experience in harmful conditions from 25 to 32 years was conducted. Emotional burnout syndrome was assessed using the methodology of V.V. Boyko. To determine personality type, a new Russian version of the DS14-RU questionnaire was used. Risk factors for the development of emotional burnout were studied using an original questionnaire.Main results. The study showed that 64.4 % of respondents had formed or were in the process of forming the second stage of emotional burnout syndrome. The majority of respondents associated key aspects of emotional burnout syndrome with emotional and moral disorientation of behavior (90.4 % of respondents), reduction of professional responsibilities (72.1 % of respondents), emotional deficit (68.8 % of workers), inadequate selective emotional response (63.5 % of miners). The prevalence of personality type D among the miners surveyed was 56.5 %, which was significantly higher than among the conventionally healthy working population.Conclusion. The specificity of emotional burnout syndrome and its leading symptoms were determined in miners working at coal enterprises in the South of Kuzbass and having a long work experience in harmful conditions. The highest values were found at the second stage of emotional burnout. A high prevalence of personality type D was found among the interviewed persons.
Keywords: emotional burnout syndrome; workers of coal enterprises; chronic stress; personality type D